ISOLATION AND CHARACTERIZATION OF BACTERIOPHAGES LYSING CLINICAL STRAINS OF E. COLI (Experimental biology, 2022)
Nosocomial infections are an important problem in modern healthcare. According to the WHO, annually, about ten million hospitalized patients die or become disabled due to nosocomial infections. One of the main causative agents of nosocomial infections are pathogenic strains of E. coli, which pose a danger to immunocompromised patients. In addition, a large number of E. coli strains have developed resistance to almost all known classes of antibiotics, which dramatically reduces the effectiveness of antibiotic therapy in the fight against such pathogens. Under these conditions, research on development of alternative approaches to combatting bacterial infections is becoming increasingly important. The most relevant and promising method is phage therapy.The purpose of these studies was to isolate bacteriophages from environmental objects capable of lysing clinical strains of E. coli, and to study their biological properties.As a result of the conducted studies, it was found that environmental objects located in sanitary-unfavorable areas are the most preferable objects for the isolation of E. coli lytic bacteriophages. Six bacteriophages able to lyse the clinical strain of E. coli were isolated from samples collected in similar areas. The isolated bacteriophages were strictly species-specific and possessed maximum lytic activity at concentrations of 105 viral particles per ml or more, which is the standard for commercial phage preparations. The investigated phages showed their high antibacterial activity sufficient to effectively combat against pathogenic of E. coli strains.
Keywords: Bacteriophage; Escherichia coli; Nosocomial infection; Antibiotic resistance; Lytic activity